Шопен - Дулемба Владислав (Иллюстрированные Биографии Великих Музыкантов, 2001)
Экземпляры: ИСК (20041118) / Инвентарный номер: 1052654 / Цена: 118.50 / Сис.шифр: 85.313(3/8)-8 / Авт.знак: Д 81 / ГРНТИ: 18 / ББК: 85.313(4)-8